Macroeconomic effects of short-term training measures on the matching process in Western Germany - Reinhard Hujer; Christopher Zeiss (Institute for the Study of Labor (IZA), 2006)
This paper investigates the macroeconomic effects of short term training measures on the matching processes in West Germany. The empirical analysis is based on regional data for local employment office districts for the period from January 2003 to December 2004. The empirical model relies on a dynamic version of a matching function augmented by short term training measures. In order to obtain consistent estimates in the presence of a dynamic panel data model and endogenous regressors, GMM estimation methods are applied.
urn:nbn:de:101:1-2008051309
Keywords: 330